Policing the Second Amendment guns, law enforcement, and the politics of race - Carlson, Jennifer (Princeton University Press, 2020)
An urgent look at the relationship between the politics of guns, race, and policing in America todayThe United States is steeped in debates about guns. As discussions rage on, one issue has been overlooked—Americans who support gun control turn to the police as enforcers of their preferred policies, but the police themselves disproportionately support gun rights over gun control. How does this perspective shape what is considered lawful force? Who can engage in legitimate violence and who is punished for it? Linking the politics of guns with the politics of policing, Policing the Second Amendment unravels the complex relationship between public law enforcement, legitimate violence, and race. Jennifer Carlson shows how racial dynamics shape police thinking about gun laws, and, on a wider level, she examines how racial ideologies of violence profoundly influence arguments about gun use, whether by the police or civilians.Drawing on local and national newspapers, interviews with close to eighty police chiefs across the country, and observations of gun licensing processes, Carlson explores the ways the police make sense of guns and looks at how guns are regulated in different states. She describes a troubling paradox that characterizes the state of guns today—alongside unprecedented civilian access to own, carry, and use guns in order to maintain social order, there exists an all-too-visible system of gun criminalization aimed primarily at people of color. This framework informs and justifies how law enforcement pursue public safety and understand their roles in today’s policed society.From the National Rifle Association to tough-on-crime law enforcement, Policing the Second Amendment demonstrates that the terrain of gun politics must be reevaluated if there is to be any hope of mitigating further tragedies